Light Signs, the Work of Teófilo Rego for Neolux - PINTO, Miguel Moreira (2015)
The subject of our paper is the work carried out by the Portuguese photographer Teófilo Rego (1913/1993), between the 1950s and the 1960s, for the manufacturing company of neon signs Neolux. Among the universes of the professional commission and the themes that, on his own initiative, explores in his personal work, the text addresses the images that may be considered as catalogue photography, reportage and architectural photography, and that remember us a time when, all over the world, the neon advertising was part of the urban landscape – from New York to Paris, Madrid, Lisbon and, in this case, Oporto. The article analyses the history, the type and the goals of the different advertising and light signage, the effect produced by their presence in city, and discusses the many images suggested and reminded by these photographs.